Effect of polypyrrole on electrochemical properties of MWCNTs films prepared by DC-EPD technique / Nur Amira Jaaffar - Jaaffar, Nur Amira (2017)
Supercapacitors have emerged with the potential to enables major advance for energy storage. It is attractive applications where it has high energy density, fast charge- discharge time and high specific capacitance. Multi-walled carbon nanotubes (MWCNTs) usually used as electrode materials for supercapacitors. However, specific capacitance, energy density and charge-discharge time of MWCNTs itself cannot achieve the needs of supercapacitors. So, in order to overcome this situation conducting polymers was introduced. The type of conducting polymer used was polypyrrole (PPy). The colloid were prepared into two portion which is with PPy and without PPy. From the morphology characterization by FESEM, the addition of PPy has show successfully deposited on MWCNTs film. In order to prove it, the characterization of functional group by FTIR shows the wavenumbers of PPy on MWCNTs were 1624 cm'1, 1270 cm'1, 1000 cm'1 and 988 cm'1. FESEM image reveal PPy were deposited on the surface of MWCNTs. The addition of PPy have enchance the specific capacitance, energy density, power density and energy efficiency of MWCNTs. This can be observed from CV-CD measurements where nanocomposites film has the highest specific capacitance which is 25.867 Fg'1, energy density 2.6190 Whkg'1, power density 1407.22 Wkg'1 and energy efficiency 69.9 % compared to PPy film and MWCNTs film.